Exploring associations between maternal adverse childhood experiences and child behavior. (December 2018) - Stepleton, Kate; Bosk, Emily Adlin; Duron, Jacquelynn F.; Greenfield, Brett; Ocasio, Kerrie; MacKenzie, Michael J.
Abstract: Adverse childhood experiences (ACEs) are linked to many negative outcomes for adults, but scant research has examined their intergenerational effects. This study's purpose is (1) to identify whether an association exists between maternal ACEs and children's psychosocial functioning, and, if so, (2) to delineate whether such an association is linked to age in a sample of families involved with the child welfare system ( N = 259). The relationship between maternal ACEs and child behavior was assessed using OLS regressions, and significant, positive associations were found linking the number of maternal ACEs and children's standardized Child Behavior Checklist scores, on both internalizing (B = 0.10, p < .001) and externalizing (B = 0.09, p < .001) subscales. Age was not significantly associated with CBCL scores. Findings suggest the need for deeper understanding of the pathways for intergenerational transmission of risk, improved identification of parental risk and its symptoms, use of interventions accounting for parental ACEs, and greater attention to the environmental and societal contexts placing families in risk. Highlights: Caregivers' early childhood adverse experiences (ACEs) impact caregiving. Children whose caregivers have more ACEs are more likely to have internalizing and externalizing behaviors. Caregivers' trauma should be addressed as part of child welfare interventions. When children have internalizing and externalizing behaviors, it may be useful to screen parents for trauma histories.